New normal - Same inequities or engaged Te Tiriti partnership? - Kukutai, Tahu; McIntosh, Tracey; Moewaka Barnes, Helen; McCreanor, Tim (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; mātauranga māori; tiriti o waitangi/treaty of waitangi; treaty partnership; treaty-based relationships

Recession hits Māori and Pasifika harder. They must be part of planning New Zealand's COVID-19 recovery - Moewaka Barnes, Helen; Kukutai, Tahu; McCreanor, Tim; Mcintosh, Tracey (The Conversation, 2020)
Māori knowledge, memory and cultural strength will only enhance New Zealand’s economic recovery planning – if they are listened to.
Keywords: covid-19; crown policy; discrimination; treaty obligations

The case of ihumatao: Interrogating competing corporate and indigenous visions of the future - Hancock, Frances; Lee-Morgan, Jenny; Newton, Pania; McCreanor, Tim (New Zealand Sociology, 2020)

Beyond the veil: Kaupapa Māori gaze on the non-Māori subject - Borell, Belinda; Waru Rewiri, Kura Te; Moewaka Barnes, Helen; McCreanor, Tim (Journal of Sociology, 2020)
Kaupapa M?ori methodologies in Aotearoa New Zealand have often been applied to content of immediate and direct relevance to M?ori communities. Some of these include research about aspects of cultural revitalisation or examinations of the position M?ori occupy within broader ethnic disparities, particularly in health and social outcomes. This article seeks to expand the application of Kaupapa M?ori paradigms to research topics outside ?te ao Maori? (the M?ori world). We argue that the Kaupapa M?ori theorising of a M?ori visual arts and culture scholar can provide crucial insights on white privilege in Aotearoa New Zealand with a view to addressing disparities and creating more embracing and equitable perspectives of belonging, citizenship and nationhood.
Keywords: belonging; citizenship; identity; kaupapa māori

'Pissed Off and Confused'/'Grateful and (Re)Moved': Affect, Privilege and National Commemoration in Aotearoa New Zealand - McConville, Alex; Wetherell, Margaret; McCreanor, Tim; Borell, Belinda; Moewaka Barnes, Helen (Political Psychology, 2020)
This article explores affect, colonial privilege, and the cultural politics of national commemoration in Aotearoa New Zealand. Based on focus‐group interviews around two major national days, we examine means through which feelings and emotions are deployed in ways that enable the reproduction of social advantage. Situating affect within patterns of relationship, four interrelated affective‐discursive practices are explored. In relation to Waitangi Day, agents tend to work under the rubric of anger and confusion. For Anzac Day, being grateful and moved shapes the interaction, although participants often indicate preferences towards "having a day off." Given the colonial context in which these practices circulate, analysis observes the associated freedom and ease by which affective‐discursive privilege is (re)produced. Often incongruent and rarely challenged, privilege allows associated actors to do what they want, when they want, however they want. This affective climate authorizes the ongoing reproduction of, and justification for, membership to a higher‐status ethnic group of which unearned opportunities and entitlements remain its everyday, expected currency.
Keywords: colonisation; memorialisation; national identity; white privilege